Retirement 101 : from 401(k) plans and social security benefits to asset management and medical insurance, your complete guide to preparing for the future you want - Cagan, Michele (Adams 101., 2025)
"How much do I need to retire? Can I retire early? What's the retirement age, anyway? No matter whether you're twenty-five, sixty-five, or any age in between, you probably have questions about retirement and knowing the answers is the key to planning your future. And with changes to essential retirement structures like investment accounts, social security and Medicare, it's important to stay up to date for your own benefit. Whether you want to retire as soon as possible or are looking forward to continuing to work in some form for as long as you can, Retirement 101, 2nd Edition guides you through each step as you approach this life-changing milestone. Now this 2nd edition includes updated information on: Social security and Medicare; investment account contributions; required minimum distribution rules; student debt payments; enrollment changes; and more! From how to save for the day when you stop--or scale back--working to smart investment strategies to the best states to retire in to how to calculate your benefits, Retirement 101, 2nd Editions helps you create a retirement plan to accomplish your goals whatever they are"--